The Cuban Treefrog (Osteopilus septentrionalis) in Florida - Steve A. Johnson (EDIS)
WEC218, an 8-page fact sheet by Steve A. Johnson, describes this member of the frog family Hylidae which is invasive to Florida, how to identify it, its ecology and natural history, its impact in Florida, and what homeowners can do to manage Cuban treefrogs around their home. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, May 2007.